Inclusiveness of Financial Activities of Hotel Institutions during the Covid-19 Pandemic - Melnychuk, Yuliia; Chvertko, Liudmyla (Journal of Finance and Financial Law, 2022)
Scientific work on “Inclusiveness of Financial Activities of Hotel Institutions During the Covid-19 Pandemic” aims to conduct a financial analysis of the state of the hotel services market in Ukraine and the world during the period of active progression of the Covid-19 virus infection. The purpose of the article. The aim of the work was to study the peculiarities of the financial development of the hotel industry in the pandemic in the world and in Ukraine. The methodology. The totality of research methods is a methodology for analyzing and organizing the main legislative acts and laws, namely the methods of generalization, comparison, chronology, analysis and generalization. Segment diagramming, elements of financial analysis, as a digital display of the state of the economic level of development are used to visualize the state of the hotel business market. The results of the research. The study analyzes the level of change in sales revenue from the hotel business in Ukraine. The regions of Ukraine were divided into the main tourist regions and the structure of accommodation facilities by types and specialized accommodation facilities have been developed. The scientific work considers the hotel industry as elements of the market of services of Ukraine, so the distribution of accommodation is divided into in the following regions: central region, northern region and western and southern regions. The location of hotel business establishments is appropriately structured. Conclusions that were made indicate the need to improve the quality of services while expanding their range, which is due to the ever-increasing demands of consumers in accordance with the requirements of advanced technologies. A significant expansion of the range of accommodation (apartments, villas, holiday homes, country and guest houses, chalets, etc.) will best guide different groups of tourists and diversify the types of recreation. The presented paper depicts relevant and necessary research that will help hotel business leaders to respond in a timely manner to financial threats. During the Covid-19 pandemic, it is important to monitor the state of the Ukrainian services market, timely implement all possible security measures and prevent the impact of adverse factors on the development of the hotel business.